Can Physician Gestalt Predict Survival in Patients with Resectable Pancreatic Adenocarcinoma? - Pak, Linda M. (Abdom Radiol (NY), 2018)
PURPOSE: Clinician gestalt may hold unexplored information that can be capitalized upon to improve existing nomograms. The study objective was to evaluate physician ability to predict 2-year overall survival (OS) in resected pancreatic ductal adenocarcinoma (PDAC) patients based on preoperative clinical characteristics and routine CT imaging. METHODS: Ten surgeons and two radiologists were provided with a clinical vignette (including age, gender, presenting symptoms, and pre-operative CA19-9 when available) and preoperative CT scan for 20 resected PDAC patients and asked to predict the probability of each patient reaching 2-year OS. Receiver operating characteristic curves were used to assess agreement and to compare performance with an established institutional nomogram. RESULTS: Ten surgeons and 2 radiologists participated in this study. The area under the curve (AUC) for all physicians was 0.707 (95%CI 0.642–0.772). Attending physicians with >5 years experience performed better than physicians with <5 years of clinical experience since completion of post-graduate training (AUC=0.710, 95% CI [0.536–0.884] compared to AUC=0.662, 95% CI [0.398–0.927]). Radiologists performed better than surgeons (AUC=0.875, 95% CI [0.765–0.985] compared to AUC= 0.656, 95% CI [0.580–0.732]). All but one physician outperformed the clinical nomogram (AUC=0.604). CONCLUSIONS: This pilot study demonstrated significant promise in the quantification of physician gestalt. While PDAC remains a difficult disease to prognosticate, physicians, particularly those with more clinical experience and radiologic expertise, are able to perform with higher accuracy than existing nomograms in predicting 2-year survival.